One century after: a reappraisal of the gnathos (sensu Pierce, 1914) in Larentiinae (Lepidoptera: Geometridae) - Schmidt, Olga (Zootaxa, 2015)
One century ago, F.N. Pierce in his well-known monograph on the genitalia of Geometridae (Lepidoptera), divided the family into two major subdivisions, the Gnathoi and the Agnathoi, depending on the presence or absence of the gnathos in males. In his study, Pierce assigned the Larentiinae to the Agnathoi based on the apparent absence of the gnathos in this subfamily. A re-examination of the male genitalic characters of numerous larentiine species representing 14 different tribes provided, contrary to Pierce’s results, evidence for the presence of the gnathos in Larentiinae. Illustrations of the gnathos (or its remnants) in male genitalia of selected species are provided and the value of the uncus and gnathos for inferring phylogenetic relationships is discussed.